“[…] nostram solam ex tot linguis perfectam […]”. Paul Greaves’ Grammatica Anglicana (1594) between Latin Influences and Patriotism - Ragni, Cristiano (Status Quaestionis, 2023)
This essay will focus on Paul Greaves’ Grammatica Anglicana (1594), the first English grammar of Ramist inspiration and, more generally, one of the first grammars ever written to be dedicated to the English language. By the time Greaves published his Grammatica, England had established its role as a major power on the international stage. It little surprises, therefore, that it was in those same years that academic reflections on the English language began to be produced. This essay will focus on Greaves’ Prefatory Epistle and his considerations on the morphology of Early Modern English, so as to highlight how the mediation of the Latin tradition often constituted an important filter, highlighting imitative and/or emulative mechanisms, with effects of marked syncretism.